Stable fractures of the atlas and axis in children. Issue 8 (August 1984) - Richards, P G
Abstract : Three cases of stable fractures of the atlas and axis in children are presented. All patients presented with pain, spasm of neck musculature and head tilt along with a neurological deficit. All fractures were apparently stable; with conservative treatment all symptoms and signs resolved.